Metakognisi dan Theory of Mind (ToM) - Murti, Heru Astikasari Setya (Universitas Muria Kudus, 2011)
This article is a literature review on the relationship between Metacognition and Theory of Mind (ToM). Metacognition refers to the superordinat concept consisting of at least two components, namely (1) knowledge, (2) monitoring (experience) and regulation (skills), and often refers to the procedural metacognition, while ToM can be defined as knowledge about the existence and contents of the mind (eg beliefs, desires and intentions) as well as the ability to use the knowledge to make predictions and explanations of human action. Research on metacognition and ToM showed that the research data provided some evidence that early competence of ToM can be considered as the precursor of metamemori and the acquisition of representations of the concept is probably something crucial in the development of children, which in turn enables them to think about their memory and others.